Propagação de incertezas no processo decisório de enquadramento de águas superficiais - JOSIANE BARBOSA FELIPE (2023)
Water resource planning and management tools are designed to ensure that water quality and quantity standards are adequate for the uses proposed by present and future generations. However, there are uncertainties inherent in such planning efforts, resulting from applied modeling and scenario-setting of the future. It is then necessary to quantify such uncertainties, analyzing the variability in the predicted system, so that it is possible to communicate them clearly, so that decisions can be taken with the knowledge and understanding of the inherent uncertainties. Thus, this study aims to verify the propagation of uncertainties in the decision-making process for classifying surface waters through the analysis of uncertainties in water quality modeling and the variability of probable planning scenarios. For this purpose, mathematical modeling was carried out using the Qual-UFMG Model, and empirical analysis of the uncertainties arising from the coefficients of the kinetics of deoxygenation and reaeration. It was also considered the implementation of a spectrum of probable scenarios (conservationist and developmentalist) for the occupation of a sub-basin of the Ivinhema River Basin, in Mato Grosso do Sul. The results showed that the propagation of uncertainties was reflected in the behavior of the Dissolved Oxygen parameter, which reached a variation of up to 16.85% in a stretch with punctual interference. The highest probabilities of occurrence correspond to 61.17% for Class 4 in the conservationist scenario and 64.26% for concentration ≤2.00 mg/L in the developmental scenario. On the other hand, the analysis based on the behavior of the Biochemical Oxygen Demand parameter did not show significant variability, due to the low dispersion of values. Therefore, the significant interval of uncertainty generated in the behavior of the OD parameter along the length of the watercourse incurs in greater variability of the possible classification classes. Thus, it is concluded that the propagation of uncertainties in the self-purification model may demand attention in the decision-making process of the framework, influencing the proposition of water quality class and service probability. In addition, the uncertainty arising from the prediction of human occupation in the basin also promotes different interpretations of water quality, as well as the variation of the framing classes. It turns out that knowledge of the uncertainties inherent in the modeling and planning of water resources, as well as their transmission to stakeholders, can provide greater robustness to the decision-making process.